Complexation of phycocyanin with hydroxypropyl-β-cyclodextrin and its application in blue beer containing quinoa saponins as foaming agents - Zhang, Guangjie; Zhao, Hongmei; Guan, Tianzhu; Ma, Zheng (Frontiers in Nutrition, 2023)
The inclusion complex (IC) of phycocyanin (PC) into hydroxypropyl-β-cyclodextrin (HP-β-CD) was prepared by the freeze-drying method. The spectroscopic features were evaluated by Ultraviolet-visible (UV-vis) spectroscopy and Fourier transform infrared spectroscopy (FT-IR) confirming that PC was located in the hydrophobic cavity of HP-β-CD. Consistent with the structural properties, optical microscopy (OM) and Transmission electron microscope (TEM) observed that the addition of PC subjected the IC to an aggregation state with irregular lamellar structures. Stability assessment showed that pH, heat and light tolerance of PC significantly regulated and improved due to the PC/HP-β-CD complexation. The formation of ICs was helpful to enhancing the antioxidant activity of PC. Molecular modelling suggested that the D-pyrrole ring and its associated C=C group of phycocyanin entered the HP-β-CD cavity from the wider edge. On this basis, the development of blue beer with quinoa saponins as foaming agent and ICs as colorant was explored. The addition of quinoa saponins made the foam richer and more delicate without destroying the overall taste coordination of beer. Moreover, the protective effect of HP-β-CD presents a positive impact on the stability of blue beer pigment. Hence, PC encapsulated into HP-β-CD will be an impressive approach in food-related application of PC.